História do jornalismo no Rio Grande do Norte: contribuições para um levantamento bibliográfico - Bulhões, Juliana; Sobral, Gustavo (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
In this article, we focus on the research and writing of the history of journalism in Rio Grande do Norte. It is the proposal for the initial construction of a survey of the bibliographical production on the subject. In addition to the survey, the article also proposes an alleged classification for the types of study that deal with the history of journalism - following classifications proposed by Barbosa (2010) and Sousa (2009) - to which is added, at the end, a brief reflection on this production. We understand that the history of local journalism is still an open field for research and that there is still a history of journalism to be written.